Pengembangan Dashboard Interaktif Saham LQ45 Menggunakan Pendekatan Business Intelligence Berbasis Tableau - Aulia Putri; Alit Aprilya Adhisti; Putri, Inayah Ramadiya (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to develop an interactive Tableau-based dashboard to present historical data of LQ45 stocks in an informative, concise, and accessible manner. A Business Intelligence (BI) approach was applied in the data processing pipeline, involving Extract, Transform, Load (ETL) procedures using Python, followed by visualization based on Key Performance Indicators (KPI) across three thematic dashboards: Price Performance, Trading Activity, and Investment Risk. The visualization results demonstrate that grouping KPIs into thematic dashboards effectively maps stock price trends, transaction volumes, and the balance between risk and return. KPI validation using the SMART method confirms that the indicators are specific, measurable, achievable, relevant, and time-bound. Therefore, the developed dashboard not only enhances financial data literacy but also serves as a decision-support tool for data-driven investment strategies in Indonesia's capital market.